Gas-phase thermochemical properties of some tri-substituted phenols: A density functional theory study. (January 2015) - Miranda, Margarida S.; Esteves da Silva, Joaquim C.G.; Liebman, Joel F.
Abstract : Graphical abstract: Highlights: DFT calculations were performed for trisubstituted phenols. Enthalpies of formation for phenols and phenoxyl radicals were estimated. OH homolytic BDE, acidities and adiabatic ionization enthalpies were estimated. There is a general good agreement with the few existent experimental data. Abstract: The study of the energetics of phenolic compounds has a considerable practical interest since this family of compounds includes numerous synthetic and naturally occurring antioxidants. In this work, density functional theory (DFT) has been used to investigate gas-phase thermochemical properties of the following tri-substituted phenols: 2, 4, 6-trimethylphenol, 2, 6-dimethyl-4- tert -butylphenol, 2, 6-dimethyl-4-methoxyphenol, 2, 4, 6-tri- tert -butylphenol, 2, 6-di- tert -butyl-4-methylphenol, 2, 6-di- tert -butyl-4-methoxyphenol, 2, 4, 6-trimethoxyphenol, 2, 6-dimethoxy-4-methylphenol and 2, 6-dimethoxy-4- tert -butylphenol. Molecular structures were computed with the B3LYP and the ω B97X-D functionals and the 6-31G(d) basis set. More accurate energies were obtained from single-point energy calculations with both functionals and the 6-311++G(2df, 2pd) basis set. Standard enthalpies of formation of the phenolic molecules and phenoxyl radicals were derived using an appropriate homodesmotic reaction. The OH homolytic bond dissociation enthalpies, gas-phase acidities and adiabatic ionization enthalpies were also calculated. The general good agreement found between the calculated and the few existent experimental gas-phase thermochemical parameters gives confidence to the estimates concerning the phenolic compounds which were not yet experimentally studied.